2012
DOI: 10.1186/1471-2407-12-543
|View full text |Cite
|
Sign up to set email alerts
|

PTENgenomic deletion predicts prostate cancer recurrence and is associated with low AR expression and transcriptional activity

Abstract: BackgroundProstate cancer (PCa), a leading cause of cancer death in North American men, displays a broad range of clinical outcome from relatively indolent to lethal metastatic disease. Several genomic alterations have been identified in PCa which may serve as predictors of progression. PTEN, (10q23.3), is a negative regulator of the phosphatidylinositol 3-kinase (PIK3)/AKT survival pathway and a tumor suppressor frequently deleted in PCa. The androgen receptor (AR) signalling pathway is known to play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 40 publications
5
46
1
Order By: Relevance
“…Lapointe and colleagues have reported high frequency of DNA copy number alterations (CNA) in prostate cancer lymph node metastases (LN mets) including a gain of 16p13, 8q24 and deletion of 10q23 and 16q23 (11). These CNAs represent potential prognostic biomarkers that can be assessed in routine formalin-fixed paraffin-embedded (FFPE) tissue sections using specific DNA probes by FISH (14)(15)(16)(17)(18)(19). We recently mapped the previously uncharacterized focal 16p13.3 genomic gain in primary prostate tumors and identified PDPK1 encoding 3-phosphoinositide-dependent protein kinase-1 (PDK1) as a likely driver of the gain with functional impact on prostate cancer cell migration (20).…”
Section: Introductionmentioning
confidence: 99%
“…Lapointe and colleagues have reported high frequency of DNA copy number alterations (CNA) in prostate cancer lymph node metastases (LN mets) including a gain of 16p13, 8q24 and deletion of 10q23 and 16q23 (11). These CNAs represent potential prognostic biomarkers that can be assessed in routine formalin-fixed paraffin-embedded (FFPE) tissue sections using specific DNA probes by FISH (14)(15)(16)(17)(18)(19). We recently mapped the previously uncharacterized focal 16p13.3 genomic gain in primary prostate tumors and identified PDPK1 encoding 3-phosphoinositide-dependent protein kinase-1 (PDK1) as a likely driver of the gain with functional impact on prostate cancer cell migration (20).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of PTEN is directly correlated to disease stage and with increase in disease progression from benign to malignant there is significant increase in PTEN loss [17,18]. Data on a relatively small sample cohort of 43 prostate samples, suggest that PTEN deleted tumours expressing low levels of androgen receptor may represent a worse prognostic subset of prostate cancers establishing a challenge for therapeutic management [19]. Moreover, a recently published longitudinal molecular pathology analysis of a patient who died from prostate cancer demonstrated that the lethal clone arose from a small PTENdepleted focus in the primary tumour [20].…”
Section: Discussionmentioning
confidence: 96%
“…A preponderance of evidence shows that deletion of PTEN is associated with advanced localized or metastatic disease, higher Gleason grade, and higher risk of progression, recurrence after therapy, and death from disease [57][58][59][60][61][62][63]. However, the clinical value in assessing PTEN is still unclear; studies have not demonstrated that it adds prognostic information when combined with standard clinicopathologic data.…”
Section: Pi3k Pathwaymentioning
confidence: 99%